Refining child pornography law : crime, language, and social consequences - Hessick, Carissa Byrne (Law, meaning, and violence., 2016)
The legal definition of child pornography is, at best, unclear. In part because of this ambiguity and in part because of the nature of the crime itself, the prosecution and sentencing of perpetrators, the protection of and restitution for victims, and the means for preventing repeat offenses are deeply controversial. In an effort to clarify the questions and begin to formulate answers, in this volume, experts in law, sociology, and social examine child pornography law and its consequences. Focusing on the roles of language and crime definition, the contributors present a range of views about the increasingly visible role that child pornography plays in the national conversation on child safety, as well as the wisdom of the punishment of those who produce, distribute, and possess materials which may be considered child pornography.